Realisasi Promosi Melalui Pemasaran Digital pada UMKM Homestay Komodo Mountain View di Labuan Bajo - Arsyad Aditya Arifin; Charles Frederic Lutmand Bir; Chelsea Angela; Christie Natania Harjono; Fauzan Danuwijaya; Jessica Audrey; Nasya Aurelia Susanto; Santi Rimadias (Journal of Management and Creative Business, 2025)
This community service program aims to support the development of Komodo Mountain View Homestay, a newly established business in Labuan Bajo, NTT, through digital marketing strategies. The program addresses key issues such as limited visibility and facilities. The implementation method involves planning, execution, and evaluation stages, focusing on digital marketing initiatives. Activities include creating a logo for brand identity, managing social media accounts on Instagram, registering the location on Google Maps, and producing attractive visual content. Results indicate that these strategies successfully enhanced the homestay's visibility, attracted tourist attention, and supported local economic growth. With continuous efforts, the homestay is expected to compete effectively in broader markets.